2013
DOI: 10.1080/19476337.2013.764548
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of chitosan in European eel (Anguilla anguillaL.) fillets during refrigerated storage

Abstract: In this study, the effects of chitosan extracted from Metapenaeus stebbingi shells and commercial chitosan on lipid oxidation of European eel (Anguilla anguilla L.) during refrigerated storage (þ48C) were examined. The control and treated fillet samples were analyzed periodically for pH value, free fatty acid (FFA), thiobarbituric acid (TBA) number, and peroxide value (PV). The results indicated that both chitosans significantly reduced FFA content, TBA number, and PV (P 5 0.05). It was concluded that 10 g/L o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…Yanar et al. (2013) reported the lipid content in eels from Akyatan Lagoon (Turkey) to average 23.21 g/100 g while the value for protein content is given with 15.50 g/100 g. Overall our results indicate that lipid and protein values (Figure 1) are consistent with other findings analyzing A . anguilla in Turkey.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Yanar et al. (2013) reported the lipid content in eels from Akyatan Lagoon (Turkey) to average 23.21 g/100 g while the value for protein content is given with 15.50 g/100 g. Overall our results indicate that lipid and protein values (Figure 1) are consistent with other findings analyzing A . anguilla in Turkey.…”
Section: Discussionsupporting
confidence: 90%
“…The Cd, Pb and As concentrations in the samples were found to be below the detection limits in data are given in Table 3. Yanar et al (2013) reported the lipid content in eels from Akyatan Lagoon (Turkey) to average 23.21 g/100 g while the value for protein TA B L E 2 Morphometric characteristics (sampling months, sample size, average wet total weights and total lengths) of Anguilla anguilla Linnaneus 1758 (n total = 154) content is given with 15.50 g/100 g. Overall our results indicate that lipid and protein values (Figure 1) are consistent with other findings analyzing A. anguilla in Turkey. Olgunoğlu, (2010) reported average lipid contents of 20.65 g/100 g, while Ersoy (2011) identified average protein levels with 11.9 g/100 g. In a comparable study on heavy metal residues in eels in Great Britain, Edwards et al (1999) confirms our findings that mercury content in eel muscle tissue did not correlate well with body weight or height (R 2 = .4) but did somewhat with fish length (R 2 = .63).…”
Section: Re Sultsmentioning
confidence: 99%
“…To maintain the color, quality and texture of the product stored at 4 °C, fresh shrimp were soaked in the additives for up to 48 h. The treatment at pH 8, which involved 0.25% of CSWK combined with 1% of NaHCO 3 and 2.5% NaCl, proved to be the optimal condition that led to weight gain and a cooking yield that was as high as ~18% and ~14%, respectively. Yanar et al [ 121 ] reported that commercially obtained CS or chitosan produced from Metapenaeus stebbingi shells was successfully used as a coating of refrigerated European eel. In fact, both chitosan additives significantly reduced the level of free fatty acid (FFA), PV and TBA.…”
Section: Innovative Seafood Preservation Methodsmentioning
confidence: 99%
“…Ch containing TEO resulted in a higher level of inhibition of psychrotrophic bacteria and LAB in shrimp than OEO. Yanar et al [ 210 ] tested commercial Ch or chitosan produced from Metapenaeus stebbingi shells and reported that both treatments significantly reduced the level of FFA, TBA and PV in refrigerated European eel. Mohan et al [ 206 ] evaluated the effect of Ch edible coating (1% and 2%) on the quality characteristics of filleted Indian oil sardines during chilled storage.…”
Section: Seafood Packaging Technologiesmentioning
confidence: 99%